Differences in housing wealth between U.S. military service personnel and the Civilian population—Exploring the role of financial stress - Eric Olsen; Cäzilia Loibl; Sherman D. Hanna; Andrew Hanks (PLoS ONE, 2025)
The study investigates whether frequent job-based relocations, which are typical for military service personnel, are correlated with households’ ability to accumulate housing wealth. Specifically, we investigate whether differences in homeownership rates and home equity values exist for two cohorts of military personnel, the older Korea/Vietnam and the younger post-Vietnam cohorts of servicemembers. The study accounts for individual financial stress and expectations about the economy, and controls for a rich set of demographic and socio-economic factors. Data sources are the 2022 Survey of Consumer Finances and the 2021 National Financial Capability Study. Results show that the two cohorts of military households do not differ from civilian households with regard to the home ownership rate. Greater individual financial stress on one hand and more positive economic expectations on the other hand emerge as two opposing, but stress-related factors linked to lower homeownership rates. The Post-Vietnam military personnel cohort is associated with lower home equity values compared to civilian households, but no difference was found between the Korea/Vietnam cohort and civilian households. From a policy perspective, our findings indicate that housing-focused efforts in the military, such as targeted loan products, relocation allowances, financial education and counseling programs, appear to help military households cope with the demands of military career paths and the transition to post-active life. When limiting the sample to homeowners, the data indicate lower housing wealth accumulation among the younger, Post-Vietnam era military households, compared to civilian households. As frequent military moves may prevent these households from building housing wealth while in the service, this group has had less time to accumulate housing wealth, documenting the role of housing tenure length for wealth accumulation for this unique population group.